2016
DOI: 10.1038/modpathol.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome of hepatocellular carcinoma with stemness marker under hypoxia: resistance to transarterial chemoembolization

Abstract: Hypoxia is known to be important in the generation and maintenance of stemness; however, its clinical significance is yet to be determined in human hepatocellular carcinoma. The expression of stemness (K19, EpCAM) and hypoxia (carbonic anhydrase-IX (CAIX))-related markers were investigated by immunohistochemistry in three hepatocellular carcinoma cohorts. The clinicopathologic features, response to transarterial chemoembolization, and outcomes were compared. In cohort 1 (n=14, biopsy-transarterial chemoemboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 32 publications
4
46
0
Order By: Relevance
“…We found that the histopathologic features of IRE-HCCs included sinusoid-like microvascular pattern, macrotrabecular pattern, a high proportion of tumor necrosis and fibrous stroma, and expression of stemness markers, which have been reported as characteristics of aggressive and poor prognostic HCCs [20,21,23,25,43]. Therefore, IRE might be a promising noninvasive biomarker for poor prognostic HCCs showing distinct pathologic features.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We found that the histopathologic features of IRE-HCCs included sinusoid-like microvascular pattern, macrotrabecular pattern, a high proportion of tumor necrosis and fibrous stroma, and expression of stemness markers, which have been reported as characteristics of aggressive and poor prognostic HCCs [20,21,23,25,43]. Therefore, IRE might be a promising noninvasive biomarker for poor prognostic HCCs showing distinct pathologic features.…”
Section: Discussionmentioning
confidence: 87%
“…HCCs expressing stemness markers, such as K19 and EpCAM, are reportedly associated with poor prognosis and molecular signatures of aggressive biological behavior such as S2 (Hoshida et al [34]) and G1 (Boyault et al [35]) compared to HCCs that do not express these markers [18,19,[34][35][36][37][38]. Rhee et al [23] also recently reported a close association between the expression of the hypoxia marker CAIX and stemness markers including K19 and EpCAM in HCCs. In the present study, IRE-HCCs, which showed histopathologic characteristics indicative of a hypoxic microenvironment, expressed higher K19 and EpCAM levels, despite the lack of statistical significance for K19 level (p = 0.055 after Bonferroni correction).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…TACE has been suggested as a treatment option for chemoresistant unresectable cases for which liver transplantation is not an option or as 'bridging' treatment for those patients awaiting liver transplantation (40). However, the TACE procedure may increase the risk of resistance to chemotherapy by occluding the blood flow and inducing hypoxia with a concomitant risk of invasion and recurrence through EMT due to changes in the tumor microenvironment (41). Our current results suggested that low-dose metformin (1 mM) may reduce resistance to cisplatin in hypoxic conditions that result from TACE.…”
Section: Discussionmentioning
confidence: 99%
“…This implies a relationship where increased tumor cell death indicates a more aggressive cancer. Tumor microvessels are fragile and susceptible to hypoxia, which suggests that the degree of tumor necrosis re ects the level of intratumoral hypoxia [13,14,27,28]. Measured experimentally with a polarographic needle, intratumoral hypoxia correlates with poor prognosis and sensitivity to radiotherapy and chemotherapy in solid tumors [13].…”
Section: Discussionmentioning
confidence: 99%